Civil Servants’ Pension Benefits after Death in the Perspective of NU Bahtsul Masa’il: Reconstructing Status between Tirkah, Ujrah, and Irzaq - Abdul Rohim (Lakpesdam PCNU Kota Salatiga, 2025)
The death of a civil servant (Pegawai Negeri Sipil, PNS) often triggers family disputes regarding the legal status of pension benefits: whether they constitute tirkah (the deceased’s estate) that must be distributed according to farā’iḍ (Islamic rules of inheritance), or whether they are entitlements designated for specific recipients under state regulations. This divergence in understanding may lead to intra-family conflict, particularly when pension benefits are perceived as “the fruits of one’s labor” and thus assumed to be distributable as inheritance, even though the state pension scheme for widows/widowers/children is conditional and its beneficiaries are predetermined. Against this background, the study formulates two questions: (1) what is the status of a PNS pension after death according to the NU (Nahdlatul Ulama) Bahtsul Masa’il does it fall under tirkah or should it be regarded as irzāq; and (2) what are the legal bases and methods of istinbāṭ employed by Bahtsul Masa’il NU in determining the status of PNS pensions within the conceptual distinction between tirkah, ujrah, and irzāq/rizq. This research adopts a qualitative approach through library research using a descriptive analytical method, drawing on documentary analysis of Bahtsul Masa’il NU decisions, classical and contemporary literature on Islamic inheritance law and uṣūl al-fiqh, as well as statutory regulations governing PNS pensions. The analysis proceeds deductively by deriving general inheritance principles and definitions of tirkah, and then testing them against the characteristics of pensions as conditional benefit entitlements whose beneficiaries are determined by regulation. The findings show that Bahtsul Masa’il NU classifies PNS pension benefits particularly widow/widower/child pensions as not part of tirkah and therefore not subject to inheritance distribution; rather, they are positioned as irzāq/rizq (a grant/social provision) that becomes the right of designated recipients in accordance with applicable provisions. NU’s method of istinbāṭ is reflected in its consistent adherence to the four Sunni legal schools, reliance on aqwāl al-mujtahidīn and authoritative fiqh references, and its firm delineation of tirkah as property already owned by the deceased prior to death. The study recommends coordinated dissemination to PNS families and relevant institutions (government offices, religious counsellors, the Office of Religious Affairs/KUA, and fatwa bodies) on the distinction between tirkah and pension entitlements to minimize disputes, as well as the development of practical guidelines grounded in fiqh and statutory regulations to help the public differentiate inherited assets from pension benefit rights.